The Cancellation of the Sale & Purchase Binding Deed Carried Out before a Notary by the Parties - Komarudin Komarudin; Jawade Hafidz (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to determineand analyzelegal considerations used by judges in making decisions on the cancellation of the sale and purchase binding deed carried out before a notary by the parties, to find out and analyze the legal consequences of the cancellation of the sale and purchase binding deed by the judge carried out before a notary by the parties, to find out and analyze the legal remedies that can be taken by the parties in the cancellation of the binding deed buying and selling made before a notary. This research method usesnormative juridical approach.Research specificationsin this research is descriptive analytical. Techniques and data collection in this study were carried out using library research methods. Methods of data analysis using descriptive data analysis using inductive thinking method. The results of the study show that: 1) Legal considerations used by judges in making decisions oncancellation of the deed of binding sale and purchase carried out before a notary by the parties isif one of the parties defaults and to sue based on the agreed articles. 2) The legal consequences of the cancellation of the sale and purchase binding deed by the judge carried out before a notary by the partiesare compensation, cancellation of agreement, and cancellation accompanied by compensation. 3) Legal remedies that can be taken by the parties in the cancellation of the sale and purchase binding deed made before a notary are: the buyer can make a claim for compensation in the fulfillment of a sense of justice.